The use of angiotensin-converting enzyme inhibitors in general medicine - M.L.I. Mashitisho (South African Family Practice)
Angiotensin-converting enzyme (ACE) inhibitors are a class of drugs commonly used in the management of hypertension, congestive heart failure, cerebrovascular disease, stable coronary heart disease and diabetes-associated nephropathy. ACE inhibitors are divided into three classes, namely sulphydryl-containing ACE inhibitors structurally related to captopril, carboxyl-containing ACE inhibitors structurally related to enalapril, and phosphorus-containing ACE inhibitors structurally related to fosinopril. Though these classes of drugs are important in the treatment of the above conditions, they are not without side-effects. It is very important for clinicians to be aware of these side-effects so that patients can be warned, and compliance can be improved.